Being a front-line dentist during the Covid-19 pandemic: a literature review - Hamid Reza Fallahi; Seied Omid Keyhan; Dana Zandian; Seong-Gon Kim; Behzad Cheshmi (SpringerOpen, 2020)
Abstract Coronavirus is an enveloped virus with positive-sense single-stranded RNA. Coronavirus infection in humans mainly affects the upper respiratory tract and to a lesser extent the gastrointestinal tract. Clinical symptoms of coronavirus infections can range from relatively mild (similar to the common cold) to severe (bronchitis, pneumonia, and renal involvement). The disease caused by the 2019 novel coronavirus (2019-nCoV) was called Covid-19 by the World Health Organization in February 2020. Face-to-face communication and consistent exposure to body fluids such as blood and saliva predispose dental care workers at serious risk for 2019-nCoV infection. As demonstrated by the recent coronavirus outbreak, information is not enough. During dental practice, blood and saliva can be scattered. Accordingly, dental practice can be a potential risk for dental staff, and there is a high risk of cross-infection. This article addresses all information collected to date on the virus, in accordance with the guidelines of international health care institutions, and provides a comprehensive protocol for managing possible exposure to patients or those suspected of having coronavirus.